Hematological studies - Normal values ​​in men - Hurtado, Alberto (1936)
Various hematological investigations have been made ​​on 100 healthy men, and the results compared with those obtained elsewhere, and in individuals of different races. The normal range of variability related to our environment and sea level have been set using statistical methods, in order to serve as a comparative basis for future observations.